Sounding the Museum: The Problematic of the Loudspeaker - Prior, David (Mimesis Journal, 2024)
The article focuses on the role loudspeakers have played in museum sound. It argues that loudspeakers evolved according to a ‘vococentric’ bias: (a focus on the reproduction of the voice, and the assumption of voice as a normative sounding object); and that this vococentrism continues to obscure one of the central affordances of the loudspeaker: its ability to act as a vehicle for a ‘sonic’ augmented reality. A more complete and accurate account of the affordances of the loudspeaker would identify not a ‘proxy voice’ but a proto-augmented reality machine: something uniquely bestowed to blend the mediated and the real.